Synthesis of Patchy Nanoparticles with Symmetry Resembling Polar Small Molecules. Issue 9 (22nd July 2022) - Zhang, Yan; Dong, Wenhao; Wang, Yazi; Wu, Qi; Yi, Chenglin; Yang, Yiqun; Xu, Yifei; Nie, Zhihong
Abstract: Patchy nanoparticles (NPs) show many important applications, especially for constructing structurally complex colloidal materials, but existing synthetic strategies generate patchy NPs with limited types of symmetry. This article describes a versatile copolymer ligand‐based strategy for the scalable synthesis of uniform Au‐(SiO2 ) x patchy NPs ( x is the patch number and 1 ≤ x ≤ 5) with unusual symmetry at high yield. The hydrolysis and condensation of tetraethyl orthosilicate on block‐random copolymer ligands induces the segregation of copolymers on gold NPs (AuNPs) and hence governs the structure and distribution of silica patches formed on the AuNPs. The resulting patchy NPs possess unique configurations where the silica patches are symmetrically arranged at one side of the core NP, resembling the geometry of polar small molecules. The number, size, and morphology of silica patches, as well as the spacing between the patches and the AuNP can be precisely tuned by tailoring copolymer architectures, grafting density of copolymers, and the size of AuNPs. Furthermore, it is demonstrated that the Au‐(SiO2 ) x patchy NPs can assemble into more complex superstructures through directional interaction between the exposed Au surfaces. This work offers new opportunities of designing next‐generation complex patchy NPs for applications in such as biomedicines, self‐assembly, and catalysis. Abstract : The hydrolysis and condensation of tetraethyl orthosilicate on block‐random copolymer ligands induces the segregation of copolymers on gold nanoparticles and hence governs the structure and distribution of silica patches formed on the nanoparticles, resembling the geometry of polar small molecules (e.g., H2 O, NH3 ).